Subalternità siciliana nella scrittura di Luigi Capuana e Giovanni Verga - Virga, Anita (Studi e saggi, 2017)
The volume explores the work of two classic authors such as Capuana and Verga under the lens of the postcolonial perspective, accepting the thesis of the Italian unification process as an internal colonisation process. The author investigates the effects of colonisation on the representation of the Sicilian rural life, highlighting areas of ambiguity and hybridism in the writings of Capuana and Verga. The two writers, living between the colonised world and the colonising world, sometimes take part in the realisation of the hegemonic national discourse, sometimes create counter-discourses, in a never definitive alternation that makes the texts of the two Veristi rich and fascinating.